Peran UKS Dalam Mendukung PHBS Siswa SDN di Wilayah Puskesmas Pekalongan Selatan - Jihan Nabila; Azinar, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study discusses the dynamics of School Health Efforts (UKS) in supporting Clean and Healthy Living Behavior (PHBS) of Elementary School (SDN) students in the Pekalongan Selatan Health Center area. The loss of UKS function at the Elementary School (SDN) level, low understanding and interest in UKS, and the lack of awareness of elementary school students in the Pekalongan Selatan Health Center area towards clean and healthy living practices and behaviors are the background to this study. The subjects of this study consisted of six elementary schools in the Pekalongan Selatan Health Center area, namely SDN Kuripan Lor 1, SDN Kuripan Lor 2, SDN Kuripan Kidul 2, SDN Kertoharjo 1, SDN Kertoharjo 2, and SDN Duwet. This qualitative study uses the Miles & Huberman analysis model by identifying the implementation of the UKS program, UKS teacher mentor strategies, and health center support factors that influence UKS in supporting Clean and Healthy Living Behavior in schools. The results of this study indicate that the implementation of the UKS program can run well if supported by adequate human resources, sufficient facilities and infrastructure, appropriate funding sources, and an approach that involves all parties. With collaboration between schools and health centers, it is hoped that the UKS program can be more effective in improving student health and supporting PHBS in the school environment.